Intellectual capital practices in universities - Alkhateeb, Abdullah N. A.; Liu, Yao; Cheng, Jack Kie (Global Academic Excellence, Kota Bharu, Kelantan, 2018)
Intellectual capital is a concept that increases the researcher’s attention nowadays. The intellectual capital is one of the most important keys to growth and organizations development. Intellectual capital represents the intangible assets that have used for knowledge creation and performance promotion of universities. However, success at universities depends on their intellectual capital. The main purpose of this paper is to explore the practices working of the intellectual capital at universities. Education organizations especially universities were selected because it plays an important role in the development and growth of the knowledge-intensive sector. The paper concluded that only universities in developed countries are paying high attention to intellectual capital, while other countries their universities still in the development process of intellectual capital.